Comparison of techniques for the analysis of wildfowl viscera - Pollard, D F W (Wildfowl, 1967)
Gullet and gizzard contents were analysed after water extraction and conventional extraction techniques had been applied. The results suggested that the four species of seed eaten had been digested differentially within the gizzard, due mainly to differences in their resistance to mechanical digestion. A similar order of relative resistance was observed following artificial grinding of an undigested sample from the gullet. Since the more resistant seed species accumulate within the gizzard, conventional analysis may show an undue bias towards these forms; extraction methods which sample only the gullet should overcome this problem, at the expense of some qualitative precision.